Data hiding using run length matching. (13th August 2009) - Jung, Ki-Hyun; Yoo, Kee-Young
This paper proposes two data hiding methods based on run length matching encoding. All of the proposed methods use the location of accumulated run length values where it compares the run length of the cover data with that of the secret data. The run length matching (RLM) method uses the run length table, which is constructed from the cover data and secret data. The reduced run length matching (RRLM) method calculates the difference value before making the run length encoding table. The experimental results demonstrate that RLM and RRLM have their own strengths with respect to different types of data and run length encoding value matching.